TBK1: a new player in ALS linking autophagy and neuroinflammation. Issue 1 (December 2017) - Oakes, James; Davies, Maria; Collins, Mark
Abstract Amyotrophic lateral sclerosis (ALS) is an adult-onset neurodegenerative disorder affecting motor neurons, resulting in progressive muscle weakness and death by respiratory failure. Protein and RNA aggregates are a hallmark of ALS pathology and are thought to contribute to ALS by impairing axonal transport. Mutations in several genes known to contribute to ALS result in deposition of their protein products as aggregates; these includeTARDBP, C9ORF72, andSOD1 . In motor neurons, this can disrupt transport of mitochondria to areas of metabolic need, resulting in damage to cells and can elicit a neuroinflammatory response leading to further neuronal damage. Recently, eight independent human genetics studies have uncovered a link between TANK-binding kinase 1 (TBK1 ) mutations and ALS. TBK1 belongs to the IKK-kinase family of kinases that are involved in innate immunity signaling pathways; specifically, TBK1 is an inducer of type-1 interferons. TBK1 also has a major role in autophagy and mitophagy, chiefly the phosphorylation of autophagy adaptors. Several other ALS genes are also involved in autophagy, including p62 and OPTN. TBK1 is required for efficient cargo recruitment in autophagy; mutations in TBK1 may result in impaired autophagy and contribute to the accumulation of protein aggregates and ALS pathology. In this review, we focus on the role of TBK1 in autophagy and the contributions of this process to the pathophysiology of ALS.